Analysis of the Areca Nut Agroindustry Value Chain in Padang Pariaman Regency - Saputra, Idil; Santosa; Hasbullah (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
There are two chain structures consisting of main actors and supporting actors. The structure of the first chain is Farmers ? Small Collectors, ? Large Collectors ? Exporters. At the same time, the second chain structure is: Farmers, ? Home Industry, ? Collecting agents. Areca farmers get an added value of IDR 1,647.12/kilogram with an added value ratio of 71.80%. Small collectors get an added IDR 994.46/kilogram with an added value ratio of 22.10%. Prominent collectors get an added value of IDR 702.67/kg with a value-added ratio of 13.01%. The home industry obtains an added value of IDR 16,634.07/kilogram with an added value ratio of 79.21%. Farmers get a marketing margin of IDR 1,794.19/kilogram. Small collectors earn a marketing margin of IDR 1,500/kg. Collector traders earn a large marketing margin of IDR 900/kg. The home industry earns a marketing margin of IDR 18,000/kilogram.